Allergic symptoms and sensitisation in adolescents with cows' milk allergy and atopic eczema in infancy. Issue 3 (21st June 2020) - Piippo, Sonja; Viljanen, Mirva; Savilahti, Erkki; Kuitunen, Mikael
Abstract: Background: The association between atopic sensitisation, atopic eczema (AE) and asthma is known, but distinct roles of allergies on long‐term health are unestablished. Objective: Evaluation of allergic symptoms and sensitisation in adolescents who in infancy had AE and verified cows' milk allergy (CMA) or AE and a negative CMA challenge, and controls. Methods: Children with AE, with and without CMA, from a randomised controlled study in 1999‐2001 examining the effect of probiotics on AE severity at older than 12 months of age, attended a follow‐up visit at age 16 to 18, with age‐matched controls. Data came from a questionnaire (ISAAC questionnaire), analysis of serum antigen‐specific immunoglobulin Es (IgEs), and clinical evaluation. Group comparisons were carried out ( χ 2 tests and logistic regression). Results: Fifty‐two patients with AE and CMA (AE/CMA+ group), 52 with AE and suspicion of CMA (AE/CMA− group), and 57 controls attended a study visit. IgE‐mediated sensitisation was significantly more prevalent in the AE/CMA+ group vs the controls, for horse, cat, dog, egg white and wheat ( P  < .024 for all). For birch, timothy and mugwort ( P  < .008 for all), sensitisation was more prevalent in both the AE/CMA+ group and the AE/CMA− group vs controls. On the basis of questionnaire data the AE/CMA + group reported a significantly higher lifetime prevalence of wheezing (64% vs 35% and 32%; P  = .001), noninfectious rhinitis (85% vs 62% and 56%; P  = .004), and hay fever (77% vs 52% and 33%; P  < .001) vs the AE/CMA− group and the control group, respectively. Conclusion and Clinical Relevance: Patients with AE and CMA in infancy, as opposed to patients with AE only, or controls, report more allergic symptoms and exhibit more allergic sensitisation in adolescence. This indicates that CMA in infancy is an independent risk factor of allergic disease in adolescence. Abstract : We examined the effect of cows' milk allergy (CMA), confirmed by double‐blind, placebo‐controlled food challenge in infancy, on allergic symptoms later in life. These patients reported in adolescence a significantly higher lifetime prevalence of wheeze, noninfectious rhinitis and hay fever, compared to patients with atopic eczema (AE) and a previous suspicion of CMA, and controls. These patients were also more sensitised to all tested allergens, the difference was significant compared to controls.